El vórtice soberano: salamancas, políticas de lo extraordinario y la emergencia de los huarpes en Cuyo, Argentina - Diego Escolar (Nuevo mundo - Mundos Nuevos, 2012)
The re-emergence of salamancas (ghostly, miraculous, diabolic and magical meetings) has occurred alongside the re-emergence of both huarpe and generic indigenous identity identification in the Cuyo area of Argentina. This paper analyses the relationship between the production of the notions of the real, and the constitution and de-constitution of indigenous identities and subjects around cases of salamanca re-emergence. To this end, two key moments in the relationship between salamancas, science and sovereignty will be examined: the construction of the huarpe archaeological-ethnological corpus in the salamancas of Guanacache between the 1920’s and 1930’s, and the return of indigenous salamancas in the work of contemporary historians of huarpe teleology. The article will illustrate how salamancas create a space of constitution and impugnation of identities and political relationships through the magic of history and the politics of the extraordinary.